Classification of nanomaterials for surface engineering of machinery parts - Фастовець, Павло Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The classification of nanomaterials is improved, that are used in the area of machinery parts engineering, by systematizing of development and detailization of main classification signs of nanomaterials